The Association Between Atopic Dermatitis, Vernal Keratoconjunctivitis, and the Risk of Scleritis: A Systematic Review and Meta-Analysis - Khoironi Imada; Mery Giovedi (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Scleritis is a destructive inflammatory disorder of the sclera. While traditionally associated with systemic autoimmune diseases like Rheumatoid Arthritis, the role of chronic atopic conditions—specifically Atopic Dermatitis (AD) and Vernal Keratoconjunctivitis (VKC)—remains under-synthesized. This meta-analysis aims to quantify the risk of scleritis in patients with these atopic conditions. A systematic search was conducted in PubMed, Scopus, and Google Scholar for studies published up to 2025 following PRISMA guidelines. Pooled Odds Ratios (OR) and 95% Confidence Intervals (CI) were calculated using a random-effects model. Methodological quality was assessed using the Newcastle-Ottawa Scale (NOS). Analysis of 15 eligible studies (n > 45,000 participants) revealed that patients with AD had a significantly higher risk of scleritis (pooled OR 2.45; 95% CI 1.80–3.20). VKC demonstrated an even stronger correlation with anterior scleritis (pooled OR 3.12; 95% CI 2.15–4.50). Heterogeneity was moderate (I2 = 38%), and no significant publication bias was detected. Atopy is a significant independent risk factor for scleritis. Clinical vigilance is required for patients with refractory atopic disease to prevent severe ocular complications. Keywords: Scleritis, Atopic Dermatitis, Vernal Keratoconjunctivitis, Th2-Th1 Shift, Ocular Immunology, Meta-analysis.